Variability in the chemical composition of different cottonseed and sunflower meals influences their digestibility when fed to grass carp (Ctenopharyngodon idella) - Koprucu, K. (Wiley, 2012)
In the present study, it was examined whether variability in chemical composition of different cottonseed (Nazilli-M39, Nazilli-84 and Cukurova-1518) meals (CSMs) and sunflower (Sanbro, Isera and Coban) meals (SFMs) had any effects on digestibility when fed to grass carp. Protein and energy digestibility of CSMs (83.2-86.8%; 88.7-92.5%) and SFMs (78.9-83.1%; 88.4-92%) had a coefficient of variation of 1.96% (CSMs) and 1.52% (SFMs) for protein and 1.93% (CSMs) and 1.82% (SFMs) for energy digestibility. Sum of amino acids digestibility of CSMs (83.1-86.5%) and SFMs (78.9-83.4%) had a coefficient of variation of 1.85% and 2.47%, respectively. Protein and energy digestibility of CSMs and SFMs was significantly positive affected by a range of compositional features including protein or sum of amino acids and phosphorus content, and significantly negative affected by fiber and carbohydrate contents in the test ingredients. This suggested that fiber and carbohydrate contents of CSMs and SFMs may also be influencing the nutritional value of its own protein or sum of amino acids. In conclusion, the relationship between plant protein meals protein content and its digestible value provides a good support for the development of a system of grain segregation by protein content and ingredient pricing according to that protein content.
Keywords: digestibility; energy; grass carp; nutrient; variability